Divided memory : French recollections of World War II from the liberation to the present - Wieviorka, Olivier 1960- (Stanford Univ. Press, 2012)
The work of the provisional government of the French Republic (1944-1946) -- Conciliation and tension : the work of the Fourth Republic (1946-1958) -- The Gaullist republic, a golden age? (1958-1969) -- Stormy weather (1969-1981) -- The ambivalences of the Mitterrand era (1981-1995) -- Memory assuaged? : from Jacques Chirac to Nicolas Sarkozy (from 1995 to the present)